Gyrokinetic particle-in-cell simulations of electromagnetic turbulence in the presence of fast particles and global modes. (1st October 2022) - Mishchenko, A; Bottino, A; Hayward-Schneider, T; Poli, E; Wang, X; Kleiber, R; Borchardt, M; Nührenberg, C; Biancalani, A; Könies, A; Lanti, E; Lauber, Ph; et al.
Abstract: Global simulations of electromagnetic turbulence in circular-flux-surface tokamak and ASDEX-Upgrade geometry, tearing instabilities and their combination with the electromagnetic turbulence, nonlinear Alfvénic modes in the presence of fast particles and their combination with the electromagnetic turbulence and global electromagnetic turbulence in Wendelstein 7-X stellarator geometry are carried out using the gyrokinetic particle-in-cell code ORB5 (Lanti et al 2020 Comp. Phys. Comm. 251 107072) and EUTERPE (Kornilov et al 2004 Phys. Plasmas 11 3196). Computational feasibility of simulating such complex coupled systems is demonstrated. For simplicity, the reduced mass ratio is used throughout the paper.